Perceived Mental Workload and Psychological Variables in Elite Individual and Team Bulgarian Athletes: An Exploratory Study - Antonio Núñez; Milena Kuleva; Tatiana Iancheva; Alejandro García-Mas (Psychology in Russia: State of Art)
Background. The concept of mental workload (MW) is a conceptual framework for evaluating the balance between the cognitive resources allocated to a task and those available to an individual. MWis influenced by the effort expended, the complexity of the task, and the individuals total processing capacity and resources. Objective. This paper aims to explore MW in the field of sport and its relationship with other psychological variables, such as anxiety and burnout. This approach is not widely used in this context so this analysis is considered novel and unique. Design. This paper is a cross-sectional study, with a sample selected by convenience sampling, consisting of Bulgarian athletes divided into three qualification categories: athletes competing at international competitions, athletes participating in national-level competitions, and non-professional athletes. The sample consisted of 107 athletes from various sports, with 62% male and 38% female participants. The instruments used to assess the different psychological variables included the NASA-TLX for MW and an abbreviated questionnaire derived from the SAS-2 for Anxiety and Burnout based on ABQ. Results. Athletes' mental workload is multifaceted, influenced by physical and psychological factors, which may also act as a protective factor against anxiety. Team sports show higher levels of mental workload due to contextual uncertainty (entropy), which could reduce performance anxiety. Two athlete profiles emerged: a bright side (high effort, low anxiety) and a dark side (low effort, high anxiety). Conclusion. These findings contribute to existing knowledge in sports psychology, providing deeper insights into the role of mental workload in athletic preparation and its potential function as a protective factor against anxiety.